ARE STAFFLESS ALTERNATIVE PHYTOSANITARY PRODUCTS? - Ferreira, T. C.; Oliveira, V. C. (Revista Brasileira de Engenharia de Biossistemas, 2016)
Sustainable agriculture has been increasingly used as a way to produce food sustainably and food security over to an unsustainable agricultural model. And for this are used various pesticides to combat pests and diseases occurring in these agroecosystems. Among these the most commonly used compounds are: Bordeaux mixture, the lush syrup, lime sulfur and products derived from plant secondary metabolism. However, such compounds have been criticized for the fact that safety measures must be taken when handling them. Therefore, there are still many gaps within the knowledge about the use of these products, as well as the protective measures that must be taken when using such products, so it is noted the need for many exploratory studies in order to better understand the use and the benefits that such products can provide to the human being in economic and environmental terms.